2005
DOI: 10.1158/1055-9965.epi-04-0343
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Dehydrogenase 3 and Risk of Squamous Cell Carcinomas of the Head and Neck

Abstract: In order to examine the association between alcohol dehydrogenase 3 (ADH3) genotypes and risk of head and neck squamous cell carcinomas (HNSCC), we conducted a hospital based case-control study including 348 cases and 330 controls. DNA isolated from exfoliated cells from the oral cavity were genotyped for ADH3 polymorphisms using PCR followed by SspI digestion. Odds ratios (OR) and hazards ratios (HR) were done by unconditional logistic regression and Cox regression. Relative to ADH3 2-2 carriers, ADH3 1-1 [OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 36 publications
1
22
0
1
Order By: Relevance
“…In a pooled analysis of seven published case-control studies, including 1,325 cases and 1,760 controls, no increased risk of head and neck cancer for the ADH1C valine homozygote at codon 350 or heterozygote genotypes were observed (7). Subsequent published studies on the ADH1C genotype have mostly reported null results, with studies in Brazil (18) and Iowa (19) reporting no overall association with head and neck cancer, and a study in Japan reporting no association with esophageal cancer (17). Peters et al (20) reported an increased risk of laryngeal cancer for carrying the ADH1C Val 350 allele, although no increase in overall head and neck cancer risk was observed.…”
Section: Introductionmentioning
confidence: 97%
“…In a pooled analysis of seven published case-control studies, including 1,325 cases and 1,760 controls, no increased risk of head and neck cancer for the ADH1C valine homozygote at codon 350 or heterozygote genotypes were observed (7). Subsequent published studies on the ADH1C genotype have mostly reported null results, with studies in Brazil (18) and Iowa (19) reporting no overall association with head and neck cancer, and a study in Japan reporting no association with esophageal cancer (17). Peters et al (20) reported an increased risk of laryngeal cancer for carrying the ADH1C Val 350 allele, although no increase in overall head and neck cancer risk was observed.…”
Section: Introductionmentioning
confidence: 97%
“…The 5-year survival rate after SPC diagnosis is about 8% if the malignancy is outside the head and neck area, and increased to 30% if the SPC is an HNC [25]. So far, few studies examined the prognostic significance of gene polymorphisms in alcohol metabolism and oxidative stress-related genes in patients with HNC, and they reported evidence of an association of specific polymorphisms with survival (CYP2E1, ADH3) or higher recurrence (CYP1A2) [14,15,26]. The purpose of our study is to evaluate whether two specific alcohol dehydrogenase genes [ADH1B (rs1229984) and ADH7 (rs1573496)], and established demographics and lifestyle-related risk factors for HNC, influence overall survival, recurrence, and development of SPC in HNC patients.…”
Section: Introductionmentioning
confidence: 99%
“…The ADH1C wild-type allele (ADH1C *1) oxidizes ethanol 2.5 times faster than those encoded by the ADH1C variant allele (38). Because of this, it has been hypothesized that fast metabolizers (homozygous for the fast allele of ADH1C ) of ethanol would have higher levels of acetaldehyde per gram of tissue in the colonic mucosa compared with all other tissues and would therefore be at greater risk for colorectal cancer (36).…”
Section: Introductionmentioning
confidence: 99%